1997
DOI: 10.1037/0096-1523.23.4.1061
|View full text |Cite
|
Sign up to set email alerts
|

Low-level masking in the attentional blink.

Abstract: If two targets (Tl and T2) are to be identified among other stimuli displayed in rapid serial visual presentation (RSVP), correct identification of Tl can produce an attentional blink (AB) lasting several hundred milliseconds, during which detection of T2 is impaired. Experiment 1 confirmed that omission of the item directly following Tl (the +1 item) reduces the AB (J. E. Raymond, K. L. Shapiro, & K. M. Arnell, 1992). The next 3 experiments varied the spatial and temporal relationships between Tl and the +1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
222
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(247 citation statements)
references
References 19 publications
(66 reference statements)
20
222
5
Order By: Relevance
“…It is generally thought that this effect is mediated by backward masking of T1 by the Lag 1 item (e.g., Brehaut, Enns, & Di Lollo, 1999;Seiffert & Di Lollo, 1997). Our computational model does not incorporate specific mechanisms for simulating backward masking and, hence, does not directly address the effect of T1 masking on T2 performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought that this effect is mediated by backward masking of T1 by the Lag 1 item (e.g., Brehaut, Enns, & Di Lollo, 1999;Seiffert & Di Lollo, 1997). Our computational model does not incorporate specific mechanisms for simulating backward masking and, hence, does not directly address the effect of T1 masking on T2 performance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have manipulated the spatial locations of the items in an RSVP stream and demonstrated that the attentional blink extends across space. For instance, Visser, Zuvic, Bischof, and Di Lollo (1999; see also Breitmeyer, Ehrenstein, Pritchard, Hiscock, & Crisan, 1999;Seiffert & Di Lollo, 1997;Shih, 2000) found that the identification of a second target is also impaired when it is presented to the left or right of the first target. They argued that attention cannot be switched to a new location while the system is processing the first target.…”
Section: Does the Attentional Blink Affect Spatial Processing?mentioning
confidence: 99%
“…In this sense, we could regard T1 and T2 as two communicating vessels; the more resources required for the one, the fewer are left for the other. Indeed, various studies have confirmed a negative correlation between behavioral indices or neural correlates of T1 and T2 processing (Chun & Potter, 1995, Table 1;Hommel et al, 2003;Seiffert & Di Lollo, 1997;Shore et al, 2001; see also Kahneman, 1973, p. 151). However, note that in most of our experiments, if anything, T1 detection improved when observers were associating freely (Olivers & Nieuwenhuis, 2005), listening to music (Olivers & Nieuwenhuis, 2005), doing another task (Experiment 1), or being presented with positive stimuli (Experiment 2).…”
Section: Relation To Existing Theoriesmentioning
confidence: 99%
“…Various explanations of the attentional blink have been proposed (Chun & Potter, 1995;Duncan, Ward, & Shapiro, 1994;Giesbrecht & Di Lollo, 1998;Jolicoeur & Dell'Acqua, 1998;Nieuwenhuis, Gilzenrat, Holmes, & Cohen, 2005;Raymond et al, 1992;Seiffert & Di Lollo, 1997;Shapiro & Raymond, 1994;Vogel, Luck, & Shapiro, 1998), but they all stress the limitedcapacity nature of attentional processing as the main determinant. For example, Chun and Potter (1995) proposed a two-stage theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation